Pola Pembelajaran Kitab Kuning Dengan Menggunakan Aksara Pegon di Madrasah Diniyah - Moh. Irfan (Sumbula: Jurnal Studi Keagamaan, Sosial dan Budaya, 2021)
This study describes the pattern of learning the yellow book with pegon script in Madrasah Diniyah Ghozaliyah Sumbermolyo Jogoroto Jombang. This type of research is descriptive qualitative, data collection is carried out using the methods of observation, interview, and decomentation. Data analysis used descriptive qualitative analysis, namely in the form of written data or from interviews with related parties. The results of this study indicate that the pattern of learning the yellow book with pegon script in Madrasah Diniyah Ghozaliyah Sumbermolyo Jogoroto Jombang has been going well. This is because before learning using the pegon script begins, every teacher already has steps of preparation, implementation, and follow-up activities, so that students are more responsive, smart, and careful in understanding a sentence.